Capital Adequacy Analysis of Indonesian Sharia Bank: 2015-2022 - Fitri, Amatul; Widiarni, Anis; Sari, Rani Puspita; Tanassy, Rika Putri; Sahara, Sahara (Tujjar International Journal of Islamic Economics Development, 2023)
This study aims to examine the effect of profitability (ROA), liquidity (FDR), and non-performing financing (NPF) on the Capital Adequacy Ratio (CAR). This research is descriptive qualitative research. The population and sample in this study are the annual financial statements of Bank Syariah Indonesia for the period 2015-2022 which are registered with the Financial Services Authority. Data was collected by recording documents and analyzed by interactive model analysis. The results of the study show that (1) profitability (ROA) has a negative effect on Capital Adequacy Ratio (CAR), (2) Liquidity (FDR) has an effect on Capital Adequacy Ratio (CAR), and (3) problem financing (NPF) has an effect on Capital Adequacy Ratio (CAR).